2020
DOI: 10.1029/2020jd032831
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Volcanic Aerosols on the Hydrology of the Asian Monsoon and Westerlies‐Dominated Subregions: Comparison of Proxy and Multimodel Ensemble Means

Abstract: Proxy-model comparisons show large discrepancies in the impact of volcanic aerosols on the hydrology of the Asian monsoon region (AMR). This was mostly imputed to uncertainties arising from the use of a single model in previous studies. Here we compare two groups of CMIP5 multimodel ensemble mean (MMEM) with the tree-ring-based reconstruction Monsoon Asia Drought Atlas (MADA PDSI), to examine their reliability in reproducing the hydrological effects of the volcanic eruptions in 1300-1850 CE. Time series plots … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…The monsoon circulations over the South American, South African, and Australian monsoon regions exhibit anticyclonic anomalies in the aftermath of large volcanic eruptions, which lead to significant decrease of monsoonal precipitation in their warm seasons. These results are comparable to the drying effects of past eruptions in the regional monsoons, mainly through the monsoon circulation weakening resulting from reduced land-sea thermal contrast (Colose et al, 2016;Cui et al, 2014;Dogar & Sato, 2019;Dogar et al, 2017;Gao et al, 2018;Man et al, 2014;Wegmann et al, 2014;Zambri et al, 2017;Zhuo et al, 2020). The increased precipitation over the North American monsoon region is possibly due to precipitation decrease of the Intertropical Covergence Zone (ITCZ) and an anticyclone anomaly over the Eurasian-African continental area after the strong volcanic forcing, which lead to anomalous ascending motion and enhanced North American monsoon rainfall (Figures S5 and S6).…”
Section: Atmospheric Circulation Changes In the Aftermath Of Large Volcanic Eruptionssupporting
confidence: 64%
“…The monsoon circulations over the South American, South African, and Australian monsoon regions exhibit anticyclonic anomalies in the aftermath of large volcanic eruptions, which lead to significant decrease of monsoonal precipitation in their warm seasons. These results are comparable to the drying effects of past eruptions in the regional monsoons, mainly through the monsoon circulation weakening resulting from reduced land-sea thermal contrast (Colose et al, 2016;Cui et al, 2014;Dogar & Sato, 2019;Dogar et al, 2017;Gao et al, 2018;Man et al, 2014;Wegmann et al, 2014;Zambri et al, 2017;Zhuo et al, 2020). The increased precipitation over the North American monsoon region is possibly due to precipitation decrease of the Intertropical Covergence Zone (ITCZ) and an anticyclone anomaly over the Eurasian-African continental area after the strong volcanic forcing, which lead to anomalous ascending motion and enhanced North American monsoon rainfall (Figures S5 and S6).…”
Section: Atmospheric Circulation Changes In the Aftermath Of Large Volcanic Eruptionssupporting
confidence: 64%
“…For many of the climate impacts listed above, the exact response such as the timing, magnitude or spatial heterogeneity often differs not only between climate model studies, but also between model-simulated and observed or reconstructed responses (e.g. Driscoll et al 2012;Pauling et al 2021;Wilson et al 2016;Zanchettin et al 2016;Zhuo et al 2020;Zuo et al 2021). Aerosol-climate modelling studies have also demonstrated large discrepancies in the simulated aerosol size and dispersion following past large eruptions such as the 1815 eruption of Mt.…”
Section: Knowledge Gaps Uncertainties and Future Opportunitiesmentioning
confidence: 99%
“…This framework could prove useful for future evaluations of volcanic precipitation response. Furthermore, while we focused our evaluation on the global response to volcanic aerosols, the regional precipitation response to volcanism remains poorly studied outside of a few monsoon regions (Liu et al, 2016;Zhuo et al, 2020). It also remains to be seen how the mechanisms driving post-eruption precipitation reduction vary with eruption magnitude.…”
Section: Discussionmentioning
confidence: 99%